Audio Description: Turning Access to Film into Cinema Art - Hannah Thompson (Disability Studies Quarterly, 2018)
This article reads Jacques Derrida's notion of the "supplement" alongside Georgina Kleege's influential work on blind access to the visual arts, in order to argue that audio description (AD) should be repositioned as a key cinematic feature rather than an access-driven afterthought. Analysis of instances of extradiegetic and intradiegetic audio description in films featuring blind protagonists reveals that AD can function to comment on, replicate or foreground the experience of the blind protagonist and/or the blind beholder. The most successful descriptions are those which are incorporated into the film from its inception, and which thus allow an enhanced viewing experience for both blind and non-blind filmgoers.